Handbook of Cultural Heritage Analysis - D'Amico, Sebastiano; Venuti, Valentina (Cham : Springer International Publishing : Imprint: Springer, 2022)
This Handbook covers non-invase techniques as well as digital technologies to study cultural heritage. It focuses on multidisciplinary approaches that help site managers to deal with their site form conservation to prevention. The book is conceived to foster exchanges of ideas and information and to update innovation on measurements suitable for cultural heritage across several disciplines. Contributions on measurements deriving from the large number of analytical methodologies and tools (spectroscopy, chemometrics, modeling, etc) are also of interest for the scientific community. Considering the tremendous amount of new interactive technologies which inevitably impact traditional arts, the final section of the Handbook focuses on the use of virtual reality systems in museums and archaeological sites. The Handbook will contribute to build an international network of cultural heritage scientists, architects, geophysicists, archaeologists, and soil scientists.
Introduction -- Large facilities and cultural heritage -- Archeometry and portable instruments -- Applied geophysics -- Monitoring of Cultural Heritage, 3D Survey, Models and GIS.-Conservation and Restoration.
Keywords: Geology; Geographic information systems; Geophysics; Cultural property; Archaeology; Geology; Geographical Information System; Geophysics; Cultural Heritage; Archaeology